2015
DOI: 10.1007/s00277-015-2328-9
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as frontline monotherapy in untreated hairy cell leukemia patients

Abstract: Rituximab as frontline monotherapy in untreated hairy cell leukemia patientsWe have read with great interest the recent article by Leclerc et al. [1] assessing rituximab therapy in hairy cell leukemia, following recent guidelines upon its usage in combination with or without purine analogs in relapsed/refractory disease [2,3]. The authors [1] make an important statement concerning the scarce data upon the use of frontline rituximab as monotherapy, in patients unable to receive other agents due to associated cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(18 reference statements)
0
5
0
1
Order By: Relevance
“…A small number of cases of frontline rituximab monotherapy have been recorded in the literature, with CR reported in 58% of patients [ 15 ]. Of note, rituximab retreatment has been reported to be effective [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small number of cases of frontline rituximab monotherapy have been recorded in the literature, with CR reported in 58% of patients [ 15 ]. Of note, rituximab retreatment has been reported to be effective [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab can be given as a single agent or in combination with purine nucleoside analogs. Although rituximab is associated with an OR in up to 80% of relapsed or refractory patients when used alone, other studies have demonstrated less spectacular results [52][53][54][55][56][57][58]. In several studies, rituximab was given at a dose of 375 mg/m 2 weekly for 4 --8 weeks.…”
Section: Rituximabmentioning
confidence: 96%
“…In a study by Nieva et al for patients relapsing after cladribine, four doses of rituximab produced 25% of overall response (OR) rate, only half being CRs [53]. There are only few reports on the use of rituximab alone as frontline therapy in previously untreated HCL patients [53,[56][57][58][59]. One study reports that 58% (7/12) of HCL patients, who were previously untreated mainly due to existing neutropenia, obtained CR ranging from 1 to 54 months after receiving 4 --8 weekly infusions of rituximab monotherapy.…”
Section: Rituximabmentioning
confidence: 97%
“…This is the reason for which our patient was treated with alpha-interferon, which was also indicated due to the presence of severe neutropenia and the presence of fever. Rituximab could be used instead of interferon, 375 mg/m 2 IV per week, during a month, as frontline monotherapy [3,14], but it was not invented at that time. The response rate was only 82 % (with 59 % complete hematological remissions) when it was used alone [15].…”
Section: Discussionmentioning
confidence: 99%